CONSTRUCTION OF FINANCIAL INCLUSION BEHAVIOUR MODELS IN THE IMPLEMENTATION OF FINTECH AT FISHERMEN SMEs CARITA, PURWAKARTA - Erni Prasetiyani; Resista Vikaliana (Journal of Management and Leadership, 2020)
This study discusses the recommendations for the construction of the Fintech Implementation Behavior Model for Fishermen SMEs in Carita, Purwakarta. This research uses a qualitative approach. Data collection was carried out by in-depth interviews with two informants: Chairman of the fishermen association and Mr. Amin fisherman / businessman / collectors with snowball sampling technique. The results showed there are three categories that influence the behavior of financial inclusion in the application of fintech to fishermen in Carita, Purwakarta, namely initial capital, access to financial institutions and financial management behavior. The construction of financial inclusion behavior models in the application of fintech in the Cirata Reservoir is socialization to carry out the behavior of fintech application or on attitudes - that is, consideration of the results of carrying out such behavior as well as socialization to influence behavioral intentions. Then, assistance to direct the mind set that is currently owned, becomes a new perception. In this case, subjective norms or the belief of many people to be involved in the behavior of applying fintech, becomes a strong self-confidence. Also approach or equality of perception of community leaders, with the aim of influencing the behavior codes of community groups, because social norms are considered as normative or standard provisions in one group, in this study the fishermen in Carita, Purwakarta. And ensuring the availability of access to financial institutions is absolutely essential in the application of fintech Keywords: Behavior Model, Financial Inclusion, Financial Technology, Fishermen